AMERICAN PREJUDICE IN JAMES DASHNER’S MAZE RUNNER; THE DEATH CURE - Age Aldi Putra (STBA Prayoga Padang, 2021)
Abstract This research discusses American Prejudice portrayed in a novel entitled The Maze Runner; The Death Cure. The novel talks about the rebellion which destroys the power of an organization called “wicked”. The writer is interested in picking up the novel as the subject of the research because this novel shows a rebellion against a non-government organization. This research uses a sociological approach to analyze how prejudice occurs in society. The writer uses the concept of the nature of prejudice by Gordon W. Allport. In this study, the writer used the mimetic theory that related to the condition and reality that happened in literary works. In doing this research the writer applied qualitative and descriptive methods to explain and deliver the data of this research. The writer finally found that the effect of prejudice is a conflict and it ends in regret.